2013
DOI: 10.1111/pace.12181
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Vein Puncture Without Contrast Venography for Pacemaker and Defibrillator Leads Implantation

Abstract: Our approach of axillary venipunture using fluoroscopic landmark, without contrast venography, is simple, safe, and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 12 publications
1
50
1
Order By: Relevance
“…Subsequently, various different techniques of axillary vein approach have been proposed ranging from a blind percutaneous puncture to the use of different tools such as contrast venography and ultrasound [10,[21][22][23][24][25][26]. Belott [23] described a technique for blind axillary vein puncture using anatomic landmarks by placing the needle tip fluoroscopically over the middle of the first rib prior to needle advancement through the pectoralis major muscle and maintaining this position by adjusting to a steeper needle angle when advancing to touch the rib.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, various different techniques of axillary vein approach have been proposed ranging from a blind percutaneous puncture to the use of different tools such as contrast venography and ultrasound [10,[21][22][23][24][25][26]. Belott [23] described a technique for blind axillary vein puncture using anatomic landmarks by placing the needle tip fluoroscopically over the middle of the first rib prior to needle advancement through the pectoralis major muscle and maintaining this position by adjusting to a steeper needle angle when advancing to touch the rib.…”
Section: Discussionmentioning
confidence: 99%
“…Our study used the first rib as landmark, not the second rib, and therefore this method prevented excessive bleeding at the puncture site and allowed for better and easier lead fixation. Although this could be considered as a technique sometimes used in the clinical practice, we have done a thorough literature review, and we found only one retrospective chart review published study conducted in a smaller patient population in Israel, that used the most lateral edge of the first rib as a fluoroscopic landmark [13].…”
Section: Discussionmentioning
confidence: 99%
“…Out of the small number of published data on axillary vein puncture most are non United States smaller scale studies that compare various methods, namely, the contrast venography-guided, the Dopplerguided, and the ultrasound-guided puncture methods except for a few studies done in Israel, Japan and India with fluoroscopy-guided Total device/lead change 261 approach [9,11,[13][14][15]. This study is a North-American experience with fluoroscopy-guided axillary vein puncture using the first rib as a landmark; it is done in a relatively large African-American population, and discusses the immediate complications of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Various fl uoroscopic approaches have been described with very high success rates. 4 We therefore believe that axillary venous access is safe, useful, easy to learn and therefore of use to all physicians performing central venous access techniques. ■ …”
Section: Cardiology Registrars and Permanent Pacemaker Complication Rmentioning
confidence: 95%